2019
DOI: 10.1107/s2053273318017254
|View full text |Cite
|
Sign up to set email alerts
|

Phason-flips refinement of and multiple-scattering correction for thed-AlCuRh quasicrystal

Abstract: The origin of the characteristic bias observed in a logarithmic plot of the calculated and measured intensities of diffraction peaks for quasicrystals has not yet been established. Structure refinement requires the inclusion of weak reflections; however, no structural model can properly describe their intensities. For this reason, detailed information about the atomic structure is not available. In this article, a possible cause for the characteristic bias, namely the lattice phason flip, is investigated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The mistreatment of phasons can lead to a substantial disagreement between the calculated values of the structure factor and the experimental data, even if the atomic structure is correct. In our recent work, where the analytical formula for the phason disorder was derived for the PT, we indicated that the lack of a phasonic term leads to a model with a crystallographic R > 20% for the same structure that is considered in this work (Buganski et al, 2019). The simulations indicate that the Gaussian term given by formula (3) can lead to excessive damping of the structure-factor amplitudes, resulting in a 'tail' in the F calc versus F obs plot (Buganski et al, 2015).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…The mistreatment of phasons can lead to a substantial disagreement between the calculated values of the structure factor and the experimental data, even if the atomic structure is correct. In our recent work, where the analytical formula for the phason disorder was derived for the PT, we indicated that the lack of a phasonic term leads to a model with a crystallographic R > 20% for the same structure that is considered in this work (Buganski et al, 2019). The simulations indicate that the Gaussian term given by formula (3) can lead to excessive damping of the structure-factor amplitudes, resulting in a 'tail' in the F calc versus F obs plot (Buganski et al, 2015).…”
Section: Discussionmentioning
confidence: 73%
“…The final value of the R factor decreases to 6.08%. This result would suggest that the atomic structure deviates from the perfect PT more than the analytical model of phasons (Wolny et al, 2016;Buganski et al, 2019) implies, especially if the value of the second moment is compared with the relation presented in Fig. 7.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Firstly, at this stage of the investigation the model was not refined. Secondly, the phason disorder (phason flips) is known to be a dominant factor affecting the intensity of the diffraction peak (Buganski et al, 2019).…”
Section: Figurementioning
confidence: 99%